Multi-Product Lactic Acid Bacteria Fermentations: A Review - Mora Villalobos, José Anibal (2020)
Industrial biotechnology is a continuously expanding field focused on the application of microorganisms to produce chemicals using renewable sources as substrates. Currently, an increasing interest in new versatile processes, able to utilize a variety of substrates to obtain diverse products, can be observed. A robust microbial strain is critical in the creation of such processes. Lactic acid bacteria (LAB) are used to produce a wide variety of chemicals with high commercial interest. Lactic acid (LA) is the most predominant industrial product obtained from LAB fermentations, and its production is forecasted to rise as the result of the increasing demand of polylactic acid. Hence, the creation of new ways to revalorize LA production processes is of high interest and could further enhance its economic value. Therefore, this review explores some co-products of LA fermentations, derived from LAB, with special focus on bacteriocins, lipoteichoic acid, and probiotics. Finally, a multi-product process involving LA and the other compounds of interest is proposed.